Case Study : Oldtown White Coffee Malaysia / Siti Nabilah Ruslin - Ruslin, Siti Nabilah (2020)
“White Coffee” is used to refer to regular black coffee that has had milk, cream or some other “whitener” added to it, though the term is almost entirely unheard of in the US, where the same beverage might be called “coffee light” in the New York City area, “light coffee”, “coffee with milk,” or “regular coffee” in New England and New York City. However, in Malaysia, “white coffee” often simply refers to how the drink is prepared and presented with added milk or creamer. The original white coffee in Malaysia is started in the Old Town of Ipoh and was a drink made from beans roasted in margarine, ground, brewed and served with sweetened condensed milk. Ipoh Oldtown White Coffee continues to be popular throughout the country. Local coffee manufacturers now mix instant coffee powder with non-dairy creamer or whitener and sugar, and market the 3-in-1 mixture as white coffee as well. The mixture is preferred by Malaysians at home or in the office as a convenient easy-to-prepare coffee drink.